Intimate Dynamics and Relationship Satisfaction among LGB Adolescents: The Role of Sexual Minority Oppression - Henrique Pereira; Graça Esgalhado (Children, 2021)
Adolescent lesbian, gay, and bisexual (LGB) romantic partners face the challenge of developing satisfactory relationships while managing stressors associated with being members of a stigmatized minority group due to their sexual minority status. The aims of this study were to explore and describe relationship dynamics among LGB adolescents that are in committed same-sex relationships in Portugal, to assess levels of satisfaction with their relationships, and to assess whether LGB oppression was associated with the likelihood of anticipating and experiencing problems within the relationship. A sample of 182 self-identified LGB adolescents (mean age = 17.89 years; SD = 1.99), completed an online survey consisting of various sociodemographic measures, a relationship dynamics questionnaire, a self-assessment of relationship satisfaction, and an adapted version of the Gay and Lesbian Oppressive Situations Inventory. Results show that participants were highly satisfied with their relationships, except those who were non-monogamous and less committed to their relationships. Participants showed moderate levels of LGB oppression situations, and, as demonstrated by the hierarchical multiple regression analysis, age (being older), having lower levels of commitment, and being exposed to higher levels of exclusion, rejection, and separation were strong predictors of lower levels of relationship satisfaction.